Impairment of executive functions due to sleep alterations: An integrative review on the use of P300 - Lima, Nathalya Chrispim; Kirov, Roumen; de Almondes, Katie Moraes (Frontiers in Neuroscience, 2022)
Objective: Cognitive impairment due to sleep deprivation (SD) is an important global health concern as part of the growing rates of sleep disorders and sleep deprivation worldwide. Amongst the affected cognitive processes, the effects of SD on the executive functions (EFs) show diverse methods and inconclusive or contradictory results, highlighting the importance of further research in this field. Considering this scenario, we evaluate one of the most used methods for objectively evaluating EFs on SD: the event-related potential (ERP) P300. Methods: Our study provides a comprehensive review on the use of P300 for evaluating executive functions in sleep alterations on subjects of all ages, as well as an analysis on the efficiency of P300 as an assessment method for executive functions compared to traditional neurocognitive batteries. We review the benefits of P300 application for multiple sleep/wake alterations, whether evoked in laboratory or as part of pre-existing sleep disorders. Results: We assess the diverse protocols used to elicit and complement P300, the most identified alterations in amplitude and latency, and suggest new lines of study that could benefit from P300 within the field. Conclusion: We conclude that P300 is a valuable asset for evaluating executive dysfunction under sleep deprivation both as a standalone protocol or in conjunction with subjective methods, with consistently significant results in assessing executive dysfunction in a diversity of subjects and etiologies.